2018
DOI: 10.3390/s18051314
|View full text |Cite
|
Sign up to set email alerts
|

High Sensitive pH Sensor Based on AlInN/GaN Heterostructure Transistor

Abstract: The AlInN/GaN high-electron-mobility-transistor (HEMT) indicates better performances compared with the traditional AlGaN/GaN HEMTs. The present work investigated the pH sensor functionality of an analogous HEMT AlInN/GaN device with an open gate. It was shown that the Al0.83In0.17N/GaN device demonstrates excellent pH sense functionality in aqueous solutions, exhibiting higher sensitivity (−30.83 μA/pH for AlInN/GaN and −4.6 μA/pH for AlGaN/GaN) and a faster response time, lower degradation and good stability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…To further improve the sensitivity of the emerging AlGaN/GaN HEMT-based pH sensors, some other device structures have also been developed successively. Brazzini et al [49] and Dong et al [50] proposed an AlInN/GaN HEMT structure with a thinner AlInN barrier layer that can make the 2DEG at the AlInN/GaN interface more sensitive to the change in the surface charge caused by the environment. The experimental results from Dong et al also [50] demonstrated that the AlInN/GaN device exhibited a larger current variation in terms of the pH value measurement compared with the AlGaN/GaN devices, as shown in figures 5(a)-(b).…”
Section: Ph Sensorsmentioning
confidence: 99%
“…To further improve the sensitivity of the emerging AlGaN/GaN HEMT-based pH sensors, some other device structures have also been developed successively. Brazzini et al [49] and Dong et al [50] proposed an AlInN/GaN HEMT structure with a thinner AlInN barrier layer that can make the 2DEG at the AlInN/GaN interface more sensitive to the change in the surface charge caused by the environment. The experimental results from Dong et al also [50] demonstrated that the AlInN/GaN device exhibited a larger current variation in terms of the pH value measurement compared with the AlGaN/GaN devices, as shown in figures 5(a)-(b).…”
Section: Ph Sensorsmentioning
confidence: 99%
“…Sensors using HEMTs are actively being developed. However, most applications use HEMTs as single devices [ 3 , 4 , 5 ]. HEMTs also have a fatal disadvantage in that they are vulnerable to process voltage temperature (PVT) variations.…”
Section: Introductionmentioning
confidence: 99%
“…The progress of the power electronics industry has been contingent on the level of progress in the semiconductor power device industry, otherwise known as the power electronic device industry and this particularly on the advancements in power electronic switches [ 8 ]. The power electronic switch industry has grown and improved drastically over the years and is now in a transitional phase from the more common silicon semiconductor technologies to a totally new phase of wide band gap (WBG) technologies [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. This new phase is characterized by an improvement in the various characteristics and manufacturing techniques already in place for power electronic switches [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%